Prolonged Continuous Theta Burst Stimulation to Demonstrate a Larger Analgesia as Well as Cortical Excitability Changes Dependent on the Context of a Pain Episode - Liu, Ying; Yu, Lina; Che, Xianwei; Yan, Min (Frontiers in Aging Neuroscience, 2022)
A series of neuropathic pain conditions have a prevalence in older adults potentially associated with declined functioning of the peripheral and/or central nervous system. Neuropathic pain conditions demonstrate defective cortical excitability and clear intermissions, which raises questions of the impact of pain on cortical excitability changes as well as when to deliver repetitive transcranial magnetic stimulation (rTMS) to maximize the analgesic effects. Using prolonged continuous theta burst stimulation (pcTBS), a relatively new rTMS protocol to increase excitability, this study was designed to investigate pcTBS analgesia and cortical excitability in the context of pain. With capsaicin application, twenty-nine healthy participants received pcTBS or sham stimulation either in the phase of pain initialization (capsaicin applied) or pain ascending (20 minutes after capsaicin application). Pain intensity was measured with visuo-analogic scale (VAS). Cortical excitability was assessed by motor-evoked potential (MEP) and cortical silent period (CSP) which evaluates corticospinal excitability and GABAergic intracortical inhibition respectively. Our data on pain dynamics demonstrated that pcTBS produced a consistent analgesic effect regardless of the time frame of pcTBS. More importantly, pcTBS delivered at pain initialization induced a larger pain reduction as well as a higher response rate compared to the stimulation during pain ascending. We further provide novel findings indicating distinct mechanisms of pcTBS analgesia dependent on the context of pain, in which pcTBS delivered at pain initialization was able to reverse depressed MEP, whereby pcTBS during pain ascending was associated with increased CSP. Overall, our data indicate pcTBS to be a potential protocol in pain management which could be delivered before the initialization of a pain episode to improve rTMS analgesia, potentially through inducing early corticospinal excitability changes that would be suppressed by nociceptive transmission.